GOLD Observations of Equatorial Plasma Bubbles Reaching Mid‐Latitudes During the 23 April 2023 Geomagnetic Storm - Deepak Kumar Karan; Carlos R. Martinis; Richard W. Eastes; Robert E. Daniell; William E. McClintock; Chao‐Song Huang (Space Weather)
Abstract A coronal mass ejection erupted from the Sun on 21 April 2023 and created a G4 geomagnetic storm on 23 April. NASA's global‐scale observations of the limb and disk (GOLD) imager observed bright equatorial ionization anomaly (EIA) crests at ∼25° Mlat, ∼11° poleward from their average locations, computed by averaging the EIA crests during the previous geomagnetic quiet days (18–22 April) between ∼15°W and 5°W Glon. Reversed C‐shape equatorial plasma bubbles (EPBs) were observed reaching ∼±36° Mlat (∼40°N and ∼30°S Glat) with apex altitudes ∼4,000 km and large westward tilts of ∼52°. Using GOLD's observations EPBs zonal motions are derived. It is observed that the EPBs zonal velocities are eastward near the equator and westward at mid‐latitudes. Model‐predicted prompt penetration electric fields indicate that they may have affected the postsunset pre‐reversal enhancement at equatorial latitudes. Zonal ion drifts from a defense meteorological satellite program satellite suggest that westward neutral winds and perturbed westward ion drifts over mid‐latitudes contributed to the observed latitudinal shear in zonal drifts.